A prospective study to determine the role of routine prophylactic oral calcium and vitamin D supplements in prevention of transient hypocalcaemia after total and near total thyroidectomy - Nair, Kiran Sukumaran; Gamalial, Jose; P. S., Rajesh (International Surgery Journal, 2017)
Background: Transient hypocalcaemia is a frequent complication after total thyroidectomy, and the symptoms are very distressing for the patients. This study is a prospective cohort study to assess the effectiveness of routine postoperative oral calcium and vitamin D supplementation in post thyroidectomy hypocalcaemia. Methods: 135 patients undergoing near total or total thyroidectomy were divided into two groups, exposed and unexposed, based on post-operative calcium and Vitamin D administration. Both groups were followed up at day 3, at discharge and 2 weeks post operatively for the development of hypocalcaemia. Results: Common age group was 31-40 years in both groups. The mean corrected pre-operative serum calcium was 9.06±0.43mg/dl for the exposed and 9.2±0.62mg/dl for the unexposed group (p = 0.12). The mean corrected calcium levels, on third post op day was 8.9±0.61mg/dl for exposed and 8.5±0.69mg/dl for unexposed group p = 0.001), on day of discharge was 9.2±0.56mg/dl for exposed and 9.0±0.48mg/dl for unexposed group (p = 0.019), and at 2 weeks follow-up was 9.5±0.51mg/dl for exposed and 9.2±0.63mg/dl for unexposed group (p = 0.002). Incidence of clinical symptoms of hypocalcaemia in the exposed group was 5.1% and in the unexposed group was 25.9%. Majority of these patients had transient hypo-calcaemic symptoms in the 48-72hr time period after surgery in both the groups. Conclusions: Routine prophylactic oral calcium and Vitamin D supplementation is effective in preventing transient hypocalcaemia following total or near total thyroidectomy.